Práticas jornalísticas e amplificações ficcionais no livro-reportagem Honoráveis Bandidos, de Palmério Dória - Silva, Fernando Lopes da (2018)
This research intends to discuss the concept of reportage book, focusing the relationships that these narratives establish with the journalistic texts circulating in the periodicals, on the one hand, and with the editorial system, on the other. In order to fulfill this proposition, it was chosen as object of research the analysis of the internal structure of the reportage book Honoráveis Bandidos, by the Brazilian journalist Palmério Dória. Inicia Ting his narrative in the moment that José Sarney took over the presidency of the Federal Senate (2009) for the third and last time, this reportage book relates a series of political scandals involving the protagonist and the people close to him, characterized as honorable bandits, according to the historically consecrated expression by the German philosopher Karl Marx. The reportage presented in book form is narrated with a series of procedures common to journalistic writing: data collection, citations, interviews and testimonies. In addition to the presentation of the referential elements enumerated by the journalist, the narrative emphasizes, in an ironic tone, physical and psychological characteristics of the characters, assigning them thoughts, sharing anecdotes with the readers and describing scenes and scenarios, fictionally amplifying the factual and journalistic elements. Thus, the understanding of one of the most successful book reports in the publishing market allows us to elucidate the very concept of the reportage book, understood both as a journalistic subsystem and as an editorial format.